2022
DOI: 10.3390/coatings12060790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Deposition Mode and Heat Treatment on the Microstructure and Wettability of Y2O3 Coatings Prepared by Reactive Magnetron Sputtering

Abstract: A robust hydrophobic Y2O3 coating at high temperatures is important for industrial applications. In this study, Y2O3 thin films on Si substrates were prepared by reactive direct current magnetron sputtering. By changing the deposition power, Y2O3 thin films with different microstructures were obtained in poison mode and metallic mode, respectively. In order to understand the effect of heat treatment on the microstructure and hydrophobicity of Y2O3, the samples were annealed at 400 °C in the air. Compared to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In contrast to the previously reported 158.2 and 156.2 eV, the binding energy of Y 3d is shifted to be higher by around 0.3–0.8 eV, identifying the existence of hydroxylation in the 6-nm-thick Y 2 O 3 film . The 3 nm metal yttrium was completely oxidized, because a metal Y 3d peak at 155.6 eV was not observed . There is another peak around 153 eV, belonging to silicon from the underlying SiO 2 /Si substrate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previously reported 158.2 and 156.2 eV, the binding energy of Y 3d is shifted to be higher by around 0.3–0.8 eV, identifying the existence of hydroxylation in the 6-nm-thick Y 2 O 3 film . The 3 nm metal yttrium was completely oxidized, because a metal Y 3d peak at 155.6 eV was not observed . There is another peak around 153 eV, belonging to silicon from the underlying SiO 2 /Si substrate …”
Section: Resultsmentioning
confidence: 99%
“…35 The 3 nm metal yttrium was completely oxidized, because a metal Y 3d peak at 155.6 eV was not observed. 36 There is another peak around 153 eV, belonging to silicon from the underlying SiO 2 / Si substrate. 37 O, and N−H were taken from references.…”
Section: Wafer-scale Device Fabrication and Characterizationmentioning
confidence: 99%
“…The x-ray diffraction and x-ray phase composition showed that Al 2 O 3 and Al 2 O 3 Cr on the surface were in amorphous crystalline state, the boron coating was completely amorphous, and the zirconium dioxide coating had a crystalline structure. The fact that the films are predominantly in the amorphous state is due to the absence of the external heating of the substrates to temperatures typical for phase transitions of the materials (above 1000 °C) [24]. The substrates were heated only by radiation from the evaporated targets; therein the sample temperature did not exceed 400 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Materials like calcium fluoride (CaF 2 ), magnesium fluoride (MgF 2 ), barium fluoride (BaF 2 ), and thorium fluoride (ThF 4 ) are commonly used for optical applications due to their wide transmission wavelength range, covering the ultraviolet to the midinfrared region. However, their mechanical properties may limit Boron nitride [ 99,112,113] Calcium fluoride [ 114,115] Gallium oxide [122][123][124][125][126][127] Potassium bromide [ 139] Polydimethyl siloxane [ 141] PDMS 1.42 at 700 nm 0.39-0.78 Soft -0.002 Hydrophobic Silicon [ 128] Silicon carbide [ 142,143] Yttrium oxide [ 147,148] Zinc selenide [ 128,150] Zinc sulfide [ 151,152] their use as hard coatings. MgF 2 [135] and CaF 2 [114,115] may still find application for protecting optical surfaces, but their hardness is dependent on the deposition technique.…”
Section: Fluoridesmentioning
confidence: 99%